Planned Home VBAC in the United States, 2004 to 2009: Outcomes, Maternity Care Practices, and Implications for Shared Decision Making. Issue 4 (December 2016) - Cox, K.J.; Bovbjerg, M.L.; Cheyney, M.; Leeman, L.M.
Abstract : ( Birth 2015;42(4):299–308) Approximately 32.7% of parturients in the United States had a cesarean delivery in 2013 and will have to choose between a repeat cesarean delivery or a trial of labor after cesarean (TOLAC) during subsequent pregnancies. Vaginal birth after cesarean (VBAC) rates decreased from 28.3% to 10.6% as hospitals and obstetricians stopped offering TOLAC services due to concerns regarding safety as there is risk for uterine rupture. Consequently, the proportion of home births in women who have undergone previous cesarean delivery has increased. Earlier studies using data from the Midwives Alliance of North America Statistics Project (MANA Stats) 2.0 cohort reported the outcomes of 16, 924 planned home births of which 87% undergoing a TOLAC had a successful VBAC.